Outcomes associated with conventional versus lipid-based formulations of amphotericin B in propensity-matched groups - Campbell RS; Chaudhari P; Hays HD; Taylor RJ; Nathanson BH; Bozzette SA; Horn DL (Dove Medical Press, 2013)
Rebecca S Campbell,1 Paresh Chaudhari,2 Harlen D Hays,1 Robert J Taylor,1 Brian H Nathanson,3 Samuel A Bozzette,1 David Horn4 1Cerner Research, Culver City, CA, USA; 2Astellas Scientific and Medical Affairs, Inc., Northbrook, IL, USA; 3OptiStatim, LLC, Longmeadow, MA, USA; 4David Horn LLC, Doylestown, PA, USA Background: Lipid-based formulations of amphotericin B (LF-AMB) are indicated for treatment of invasive fungal infections in patients intolerant to conventional amphotericin B (CAB) or with refractory infections. Physicians still may choose to administer CAB to such patients. We described the use of CAB and LF-AMB in this population and quantified differences in post-amphotericin B length of stay (LOS) among survivors and hospital mortality in matched patients. Methods: Data were extracted from Health Facts (Cerner Corporation, Kansas City, MO, USA) for a retrospective cohort analysis. Inpatients aged ≥18 years with evidence of fungal infection and with orders for LF-AMB or CAB on  ≥2 days from January 2001 to June 2010 were identified. Patients were required to have renal insufficiency or other relative contraindications to use of CAB, exposure to nephrotoxic agents, or evidence of a CAB-refractory infection. Multilevel (hierarchical) mixed-effects logistic regression was used to determine factors associated with initial exposure to LF-AMB versus CAB. Multivariate adjustment of outcomes was done using propensity score matching. Results: 655 patients were identified: 322 patients initiated therapy with CAB and 333 initiated treatment with LF-AMB. Compared to those initiating CAB, patients initiating LF-AMB had greater acuity and underlying disease severity. In unadjusted analyses, hospital mortality was significantly higher in the LF-AMB group (32.2% versus 23.7%; P = 0.02). After propensity score matching and covariate adjustment, mortality equalized and observed differences in LOS after amphotericin B initiation decreased. Conclusion: Among patients at risk for amphotericin B toxicity, differences between CAB and LF-AMB seen in crude outcomes analyses relate to channeling of sicker patients to initiate treatment with LF-AMB. Failing to account for differences among patients that drive clinical decision-making will result in inaccurate conclusions about the real-world effectiveness of different amphotericin B formulations. Keywords: amphotericin, outcomes, mortality, hospitalization